Aspectos celulares e moleculares do processo de interação dos vírus Dengue e Zika com o mosquito vetor - Luiza dos Santos Felix (2022)
Arboviruses are neglected diseases transmitted by mosquito vectors. Despite having received greater recognition in the last decade, the number of cases and deaths is still alarming. Dengue and Zika are viral diseases that are part of this group and have a high incidence in tropical countries. Mitigation of such diseases consists mainly of population control strategies of mosquito vectors. In Brazil, the main vector of dengue (DENV) and Zika (ZIKV) viruses is Aedes aegypti. Despite efforts to reduce cases of both diseases, the circulation of DENV and ZIKV generates frequent outbreak episodes. For this reason, studies involving the virus-vector interaction are necessary and have the potential to contribute to arbovirus control strategies. The present study evaluates the vector competence of A. aegypti populations from an endemic city (Belo Horizonte/MG) for the transmission of DENV and ZIKV in 7 days after infection (dpi) – initial infection, and 14 dpi – late infection; and describes the kinetics of viral replication at the cellular level through the morphological analysis of C6/36 cells. Our results showed that the infection patterns of A. aegypti populations are modulated according to the flavivirus studied, with no similarity between vector competence and viral load. Regarding DENV infection, depending on the analyzed population, vector competence may decrease, increase or remain the same from 7 to 14 dpi. For ZIKV, it increases or remains the same. During the course of infection, ZIKV tends to accumulate in the salivary glands of vectors, while for DENV, the accumulation of viral particles does not have a pattern, varying according to the population studied. Although DENV and ZIKV belong to the same viral family and are structurally similar, we observed differences in their infection profiles in cells of the C6/36 lineage. In the later period of DENV infection, we observed an intensification of the cytopathic effects, with reduction of actin filaments, formation of cell groups, and destruction of the monolayer. For ZIKV infection, we noticed the presence of numerous multinucleated cells. Thus, we found that the differences in the cytopathic effects vary according to the pathogen studied and the post-infection time.